Analisis Kemampuan Representasi Matematis Siswa MTs Muallimin Univa Medan Ditinjau Dari Habits Of Mind - Irwan Irwan; Cut Latifah Zahari (Program Studi Pendidikan Matematika, FSTT, Universitas Pendidikan Mandalika, 2026)
Mathematical representation skills are important for every student to have because mathematics is a language and medium of interaction that requires a way of conveying it. Mathematics is habitual, which means that students' mathematical abilities will emerge according to their habits and thought patterns. There are many factors that influence students' mathematical representation abilities, including habits of mind. This research aims to analyze students' mathematical representation abilities in terms of five levels of habits of mind performance. This research uses descriptive qualitative approach. The population in the study were all students at MTs.Muallimin UNIVA Medan. Sampling was carried out using purposive sampling technique. The research sample was all students in class IX Visual 1 Fullday at the school with a total of 30 students. Instruments used: (1) mathematical representation ability test; (2) level habits of mind and (3) interviews. Data analysis was carried out using data triangulation. The research results show: (1) at the beginner's habits of mind performance level, students' mathematical representation abilities are not visible; (2) at the limited habits of mind performance level, students' mathematical representation abilities are visible but have no meaning; (3) at the developing habits of mind performance level, students' mathematical representation abilities are visible but there are still some errors; (4) at the level of proficient habits of mind performance, students' mathematical representation abilities are visible but still need a little improvement; (5) at the superior habits of mind performance level, students' mathematical representation abilities are visible and highly adequate in solving problems.